Risk of complications due to anticoagulation during dermatosurgical procedures: a systematic review and meta‐analysis. (30th July 2014) - Nast, A.; Ernst, H.; Rosumeck, S.; Erdmann, R.; Jacobs, A.; Sporbeck, B.
Abstract Background Management of anticoagulation and anti‐platelet drugs during cutaneous surgery is still a challenge for many dermatologists and standards of care with respect to stopping, continuing or bridging vary widely. Methods We performed a systematic review (Medline, Cochrane Library, until August 27th, 2013) of studies assessing the risk of complications due to anticoagulation during cutaneous surgery. Primary outcomes were mild‐moderate and severe postsurgical bleeding. The secondary outcomes were excessive and uncontrollable intraoperative bleeding and other postsurgical complications as wound dehiscence, erythema, wound infection. Results 1.287 publications were identified and 10 studies were included into the review. The frequencies of bleeding in the control groups in general were low (about 1%). In patients on aspirin, increased risks were seen neither with respect to mild‐moderate postoperative bleeding (RR 1.1, CI 0.5–2.3), nor with respect to severe bleeding (RR 0.9, CI 0.2–4.6). The studies with patients on warfarin showed a risk for mild‐moderate bleeding that was three times as high as in controls (RR 3.2, CI 1.4–7.1) and for severe bleeding that was 15 times higher (RR 14.8, CI 2.7–80.4). In general the study sizes were small and the methodological quality low. Conclusion The risk of bleeding due to a medication with aspirin seems to be negligible. With warfarin, the risk is increased; an exact estimate of the risk increase is difficult to give, because of the lack of sufficient high quality studies. A two‐fold increase appears likely, the 15‐fold increase is most likely due to statistical reasons arising from the rareness of the event in the small number of included patients. Stopping, bridging or continuing a medication should always be an individual decision. In accordance with guidelines from internal medicine for most patients it will be recommendable to continue with the medication.